Obesity survival paradox in pneumonia: a meta-analysis - Nie, Wei; Zhang, Yi; Jee, Sun Ha; Jung, Keum Ji; Li, Bing; Xiu, Qingyu (BMC medicine, 2014)
It is unclear whether an 'obesity survival paradox' exists for pneumonia. Therefore, we conducted a meta-analysis to assess the associations between increased body mass index (BMI), pneumonia risk, and mortality risk. Cohort studies were identified from the PubMed and Embase databases. Summary relative risks (RRs) with their corresponding 95% confidence intervals (CIs) were calculated using a random effects model. Thirteen cohort studies on pneumonia risk (n = 1,536,623), and ten cohort studies on mortality (n = 1,375,482) were included. Overweight and obese individuals were significantly associated with an increased risk of pneumonia (RR = 1.33, 95% CI 1.04 to 1.71, P = 0.02, I(2) = 87%). In the dose-response analysis, the estimated summary RR of pneumonia per 5 kg/m(2) increase in BMI was 1.04 (95% CI 1.01 to 1.07, P = 0.01, I(2) = 84%). Inversely, overweight and obese subjects were significantly associated with reduced risk of pneumonia mortality (RR = 0.83, 95% CI 0.77 to 0.91, P < 0.01, I(2) = 34%). The estimated summary RR of mortality per 5 kg/m(2) increase in BMI was 0.95 (95% CI 0.93 to 0.98, P < 0.01, I(2) = 77%). This meta-analysis suggests that an 'obesity survival paradox' exists for pneumonia. Because this meta-analysis is based on observational studies, more studies are required to confirm the results.